A Mixed-Method Study on Pre-Service Teachers' Informal Reasoning Regarding Nuclear Energy Use - Saǧlam, Halil Ibrahim; Eroǧlu, Baris (Journal of Turkish Science Education, 2022)
The aim of this study was to reveal pre-service teachers' informal reasoning regarding nuclear energy use in terms of informal reasoning modes, decision modes, and argument types. The exploratory sequential mixed method was used to collect data. The informal reasoning of pre-service teachers was investigated thoroughly and holistically by examining the qualitative data first, and then by making qualitative findings quantitative. The findings revealed that pre-service teachers adopted social and ecological-oriented informal reasoning more. As far as argument modes are concerned, the number of supportive arguments was higher compared to rebuttal arguments. The study further revealed that most of the pre-service teachers had a high level of informal reasoning. Our study showed that pre-service science teachers used multiple informal reasoning modes and demonstrated high-quality informal reasoning. Integrating socio-scientific issues in the curriculum may help pre-service teachers improve the quality of their informal reasoning and produce more arguments. Teachers can relate a subject in their lessons to a socio-scientific issue, which can help enhance students' use of arguments and the quality of informal reasoning.